Gestire il rischio idrogeologico in ambiente GIS con GPS e dati ad alta definizione - Nicotera, Fabio; Maso, Massimo (GEOmedia, 2009)
GPS and GIS integrated technologies to manage hydrogeological risk The available data and those obtained in-the-field using new technologies, as the satellite remote sensing method, based on GPS, were used to fill a database for a Geographical Information System and allowed the generation of a high resolution digital elevation model. After this, a static hydrometric height simulation model was applied to verify the correct flood risk using historical or calculated hydrometric heights. This method, based on integrated technologie illustrated which part of the reference area is under threat of being invaded by flood waters. Finally, a comparison between the extension of this area and those considered at high risk by local legislation, concluded this work.